A qualitative investigation of Orthorexia Nervosa among U.S. college students: Characteristics and sociocultural influences. (1st July 2021) - White, Mika; Berry, Rachel; Sharma, Aditi; Rodgers, Rachel F.
Abstract: Background: Current studies on Orthorexia Nervosa (ON) are predominantly correlational and have largely been conducted outside of the U.S. with little attention to cultural aspects. This study aimed to qualitatively examine ON-related attitudes and behaviors among U.S. college students, with a particular focus on exploring concerns related to healthy eating and diet quality as defined by proposed diagnostic criteria, body image concerns and disordered eating, and sociocultural influences. Method: Eighteen women and 3 men, aged 18–23 years ( M  = 19.5, SD  = 1.6), who had reported high levels of ON symptoms participated in individual interviews. Interviews were transcribed verbatim and examined for evidence of the proposed diagnostic criteria of ON. In addition, thematic analysis was conducted to examine concurrent body image and eating concerns, as well as sociocultural influences. Results: The patterns of the presence of diagnostic criteria varied, with the importance of food quality, and associated severely restricted eating patterns emerging as some of the most common elements. Six themes emerged from the thematic analysis: healthy eating concerns and diet quality, frequency and nature of food-related thoughts, definitions of healthy eating and healthy foods, disordered eating and body image, interpersonal social influence, and media and other influence from the broader social context. Discussion: The findings suggest that ON symptoms may be concurrent with, or an evolution of other eating disorder presentations. In addition, our results highlight the role of family and sociocultural factors in ON, pointing to the usefulness of examining these behaviors within sociocultural frameworks that have been successfully applied to other types of disordered eating.